2001
DOI: 10.1177/00220345010800011101
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Early in vitro Response to Actinobacillus actinomycetemcomitans Suggests Superantigenic Activation of T-cells

Abstract: The mode of T-cell response to Actinobacillus actinomycetemcomitans is largely unknown. The present study sought to investigate the hypothesis that A. actinomycetemcomitans expresses superantigens, capable of antigen-non-specific T-cell activation. To that end, peripheral blood mononuclear cells were stimulated with A. actinomycetemcomitans, and T-cell expression of the early activation marker, CD69, was determined by flow cytometry. Results showed that A. actinomycetemcomitans activated a large number of T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…A. actinomycetemcomitans has been reported to produce an as yet unidentified superantigen that rapidly causes T-cell apoptosis. 33,34) Ten, et al reported that periodontitis patients infected with A. actinomycetemcomitans harbored A. actinomycetemcomitans-specific T-cells in peripheral blood, and T-cells expressed RANK ligand (RANKL) in response to A. actinomycetemcomitans. 35) RANKL from T-cells stimulates vascular smooth muscle cells (VSMC) to produce matrix metalloproteinase-9 (MMP-9), which destabilizes atherosclerotic plaques 36) and recently was reported to be elevated in coronary artery plaque in patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…A. actinomycetemcomitans has been reported to produce an as yet unidentified superantigen that rapidly causes T-cell apoptosis. 33,34) Ten, et al reported that periodontitis patients infected with A. actinomycetemcomitans harbored A. actinomycetemcomitans-specific T-cells in peripheral blood, and T-cells expressed RANK ligand (RANKL) in response to A. actinomycetemcomitans. 35) RANKL from T-cells stimulates vascular smooth muscle cells (VSMC) to produce matrix metalloproteinase-9 (MMP-9), which destabilizes atherosclerotic plaques 36) and recently was reported to be elevated in coronary artery plaque in patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding V␤12 specifically, it has been shown that staphylococcal enterotoxin B preferentially induces the production of Th1 cytokines in TCR V␤12 T cells from healthy subjects and the production of Th2 cytokines in cells from atopic dermatitis patients (26). Also, an Actinobacillus actinomycetemcomitans extracellular preparation activated TCR V␤12 T cells (54). The identification of similar antigens in Leishmania is still deficient, probably due to the complexity of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study by Leung and Torres 35 demonstrated that P. intermedia strain 17, which is a clinical isolate, induced the strongest expansion of CD4 + T‐cell subsets that express Vβ8, Vβ12, and Vβ17 TCRs. Furthermore, to confirm the role of A. actinomycetemcomitans –derived SAg, Zadeh et al 36 conducted an in vitro study using peripheral blood mononuclear cells. These cells were stimulated with A. actinomycetemcomitans , and T cells expressing an early activation marker, namely CD69, were demonstrated through flow cytometry–based detection.…”
Section: Role Of Sagsmentioning
confidence: 99%
“…They further reported that the response to this bacterial stimulus was a large‐scale T‐cell activation in a Vβ‐specific manner demonstrating the superantigenic property by A. actinomycetemcomitans. 36 …”
Section: Role Of Sagsmentioning
confidence: 99%